ECOLOGY AND DIVERSITY OF WILDLIFE IN THE ECO-PARK OF THE JAMUNA BRIDGE AND ITS ADJACENT AREA, SIRAJGONJ, BANGLADESH - Rahman, Hasibur; Jaman, M. Firoj; Rahman, Md. Saidur (Ecoprint: An International Journal of Ecology, 2014)
Animal diversity of an area is a good indicator for understanding a healthy habitat. We conducted a detail study on ecology and the wildlife diversity in the Eco-park of Jamuna bridge and its adjacent area of Sirajgonj district from April 2010 to March 2011. We employed transect line method and interviewed local people to reveal the status and distribution of wild animal and identify their microhabitats. A total of 89 species of wild animals was recorded, of which, 6 (6.74%) species were amphibians, 11 (12.36%) reptiles, 56 (62.93%) birds and 16 (17.94%) mammals. Regarding relative abundance, 18 (20.22%) species of wildlife were very common, 35 (39.33%) common, 28 (31.46%) fairly common, 7 (7.87%) few and only one (1.12%) was occasionally found. In total 25 species of wildlife were identified as threatened category. In amphibians, 3 species were vulnerable nationally. In reptiles, 4 species were vulnerable and one endangered. In birds, 4 species were vulnerable, 6 endangered and one critically endangered (Gallicrex cinerea). In mammals, 3 vulnerable and 3 endangered nationally. Among the amphibians, skipper frog (Euplyctis cyanophlyctis) and toad (Bufo melanostictus) frequently occurred. Among the reptiles, common garden lizard (Calotis versicolor), common skink (Mabuya carinata) and cheekered keel back water snake (Xenochorphis piscator) were frequently occurred. Among the birds, common myna (Acrodotheres tristis), pied myna (A. fuscus), black drongo (Dicrurus macrocercus) and house crow (Corvus splendens) occurred frequently. Among the mammals, shrew (Suncus murinus), flying fox (Pteropus giganteus) and black rat (Rattus rattus) frequently occurred. Our study shows that illegal exploitation of trees, overgrazing of domestic animals, shooting and collection of young animals are the mentionable causes for declining wild animals. We suggest that awareness creation and preparation of proper management action plan in cooperation with related national and international organizations are necessary in order to protect the wildlife resources in the study area. DOI: http://dx.doi.org/10.3126/eco.v20i0.11327 Ecoprint: An International Journal of Ecology Vol. 20, 2013Page : 27-36